Impact of the “Public Procurement Rules, 2008” on the implementation of development projects-A Case Study on the National Board of Revenue - Rahman, Md. Zillur (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2020.